PENGATURAN TINDAK PIDANA CYBER PROSTITUTION DALAM UU NO. 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (UU ITE) - Hertati Tambunan, Susi; Dedy Priyanto, I Made (Kertha Wicara : Journal Ilmu Hukum, 2014)
The advancement in science and technology provides a lot of conveniences for people in performing daily activities, even in committing crimes. One of the crimes that are being committed over the Internet is cyber prostitution which offers sexual services through cyberspace. The cyber prostitution which regulated through the Act Number 11 of 2008 on Information and Electronic Transaction, states the element of "without authorization" and "inaccessibility of Electronic Information and/or Electronic Document which violates decency", but those two elements are not clearly regulated which create the fuzzy norm.
Keywords: Prostitution, Without Authorization, Inaccessibility of Electronic Information, Act Number 11 of 2008 on Information and Electronic Transaction